Building a multi-institutional and interdisciplinary team to develop a zoonotic tuberculosis roadmap - Olea-Popelka, Francisco, author; Fujiwara, Paula I., author; Frontiers in Public Health, publisher (Colorado State University. Libraries, 2018)
Tuberculosis (TB), as the major infectious disease in the world, has devastating consequences for not only humans, but also cattle and several wildlife species. This disease presents additional challenges to human and veterinary health authorities given the zoonotic nature of the pathogens responsible for the disease across species. One of the main public health challenges regarding zoonotic TB (ZTB) caused by Mycobacterium bovis is that the true incidence of this type of TB in humans is not known and is likely to be underestimated. To effectively address challenges posed by ZTB, an integrated One Health approach is needed. In this manuscript, we describe the rationale, major steps, timeline, stakeholders, and important events that led to the assembling of a true integrated multi-institutional and interdisciplinary team that accomplished the ambitious goal of developing a ZTB roadmap, published in October, 2017. It outlines key activities to address the global challenges regarding the prevention, surveillance, diagnosis, and treatment of ZTB. We discuss and emphasize the importance of integrated approaches to be able to accomplish the short (year 2020) and medium term (year 2025) goals outlined in the ZTB roadmap.
Keywords: zoonotic; tuberculosis; roadmap; public health; integrated; approach